Österreichische Gegenwartskunst aus der Sammlung bauMax. (Klosterneuburg : Schörmer/bauMax Gruppe, 1987)
Attersee, Christian Ludwig ; Bramer, Josef ; Brauer, Arik ; Breiter, Herbert ; Brus, Günter ; Hoke, Giselbert ; Hradil, Rudolf ; Korab, Karl ; Krawagna, Peter ; Rainer, Arnulf ; Ringel, Franz ; Salzmann, Gottfried ; Schmögner, Walter ; Zadrazil, Franz
boek
Keywords: Oostenrijk